Kegiatan Outbound untuk Membangkitkan Semangat Teamwork dan Menambah Energi yang Baru Pada Anggota MDMC Pangandaran - Nandhini Hudha Anggarasari; Rikha Surtika Dewi (ABDIMAS: Jurnal Pengabdian Masyarakat, 2018)
MDMC (Muhammadiyah Disaster Management Center) is one of the disaster management institutions under the Persyarikatan Muhammadiyah. One of the MDMCs, who were in Pangandaran lacked volunteers from Muhammadiyah's orthomal cadres. This is due to lack of collaboration with orthom and lack of socialization about disasters. Therefore, the author offers a solution to establish collaborative work with all Muhammadiyah orthoms in Pangandaran Regency, conduct outbound activities to increase cooperation, and provide socialization about disasters. The community service activities included material on disaster socialization in Pangandaran, exploring the potential and disadvantages of each organization, the importance of cooperation and communication both internally and externally on the organization, and vertical rescue training to add new insights and energy about one of the skills needed by disaster volunteers . This community service provides a positive impact on MDMC members. Collaboration built in institutions motivates members to collaborate with other organizations and fosters new enthusiasm and ideas for collaborating in humanitarian activities, especially related to the disaster in Pangandaran.